Analisis Debt To Equity Ratio, Net Profit Margin Dan Total Aset Turnover Dalam Mengukur Kinerja Keuangan Perusahaan Sub Sektor Food And Beverage Yang Terdaftar Di BEI Periode 2019 – 2021 - Dhea Emilia Purbasari; Anwar Bowo Leksono; Suseno Hendratmoko (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
Food and beverage sub-sector companies are an industrial sector that operates in the food and beverage sector. Some of them are PT Mayora Indah Tbk with net profit income in 2020 of 8.57%, then in 2021 it showed a decline to 4.33%, then there is PT Ultrajaya Milk Industry and Trading Company with net profit income which experienced an annual increase of up to 2021 amounted to 19.16%, next at PT Sekar Bumi Tbk with a very low net profit percentage compared to its competitors and only recorded 0.77% as its largest net profit in 2021, next at PT Sariguna Primatirta Tbk with increased net profit income every year with a percentage of 16.37% as the largest net profit in 2021, and most recently PT Akasha Wira International with a net profit that increased every year and recorded in 2021 the largest net profit, namely 16.37%. One way of research on financial performance can be done using ratio analysis. The research method used is a descriptive quantitative research method that analyzes the financial performance of companies in the food and beverage sub sector using Debt to Equity Ratio, Net Profit Margin, Total Asset Turnover analysis. The research was conducted from the 2019-2021 period. Based on research results, the debt to equity ratio is only at PT Sekar Bumi which shows unfavorable conditions due to the large amount of loan capital to generate profits. Based on the analysis of net profit margins in 5 companies, conditions can be said to be good. Based on total asset turnover in 5 companies, it has experienced ups and downs but can still be said to be in good condition.